Importance of P450 reductase activity in determining sensitivity of breast tumour cells to the bioreductive drug, tirapazamine (SR 4233). - Patterson, A. V. (Nature Publishing Group, 1995)
P450 reductase (NADPH:cytochrome P450 reductase, EC 1.6.2.4) is known to be important in the reductive activation of the benzotriazene-di-N-oxide tirapazamine (SR 4233). Using a panel of six human breast adenocarcinoma cell lines we have examined the relationship between P450 reductase activity and sensitivity to tirapazamine. The toxicity of tirapazamine was found to correlate strongly with P450 reductase activity following an acute (3 h) exposure under hypoxic conditions, the drug being most toxic in the cell lines with the highest P450 reductase activity. A similar correlation was also observed following a chronic (96 h) exposure to the drug in air but not following acute (3 h) exposure in air. We have also determined the ability of lysates prepared from the cell lines to metabolise tirapazamine to its two-electron reduced product, SR 4317, under hypoxic conditions using NADPH as an electron donor. The rate of SR 4317 formation was found to correlate both with P450 reductase activity and with sensitivity to tirapazamine, the highest rates of SR 4317 formation being associated with the highest levels of P450 reductase activity and the greatest sensitivity to the drug. These findings indicate a major role for P450 reductase in determining the hypoxic toxicity of tirapazamine in breast tumour cell lines. IMAGES: